DEEPENING CONDITIONS OF PRECARITY IN THE KOREAN GAME INDUSTRY AND COLLABORATIVE STRATEGIES TO OVERCOME CONSTRAINTS. - Sangkyu Lee (Kritika Kultura, 2019)
This paper examines how Korean game developers have been experiencing deepening conditions of precarity and makes a few suggestions regarding how they could overcome their structural limitations. Despite the remarkable growth in the Korean game industry, many underlying problems overshadow its success, such as labor exploitation, low wages, employment instability, and alienated labor. This paper uses a qualitative methodology to investigate the implications of the game industry market's transition from PC online to the mobile game platform since the 2010s, which contributed to the industry's deteriorating working condition and production system. Given this context, this study explores how the game developers experienced deepening conditions of precarity. This paper offers a few suggestions about overcoming these structural constraints. First, game developers can appropriate their know-how and resources then integrate them into a new form of "digital creative labor," which refers to networked and collaborative cultural practices of game developers. Secondly, this paper argues that the intervention at the institutional and policy level is necessary to protect the rights and interests of workers.